SigniFYIng APIs in the context of Polystore systems: a case study with BigDAWG - Gracioli Neto, Carlos; Salgado, Luciana; Ströele, Victor; de Oliveira, Daniel (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Polystore systems are a new trend in Database Management Systems, and they focus on storing and processing queries in multiple heterogeneous databases. Polystore systems have complex middleware that provides APIs for multiple types of storage engines. When database administrators use an API, they play the role of an application user and more attention should be paid to analyzing these APIs. This paper investigates the communicability of a Polystore system API (BigDAWG), with the SigniFYIng APIs method, from Semiotic Engineering. We analyze the potential of the method in the characterization of the communicative strategies of the BigDAWG system. The study is preceded by a simplified systematic mapping study in the area of semiotic inspection of APIs to characterize the main contributions. The results of this research indicate the applicability of the SigniFYIng APIs method to support investigations in the context of Human-Centered Computing and for the study of communicability in Polystore systems.